Heart. (January 2016) - Colvin, M.; Smith, J. M.; Skeans, M. A.; Edwards, L. B.; Callahan, E. R.; Snyder, J. J.; Israni, A. K.; Kasiske, B. L.
ABSTRACT: As the number of candidates listed for heart transplant continues to rise, it is encouraging that the number of heart transplants also continues to rise steadily each year. Evaluation of waitlist activity demonstrates a growing number of adult candidates removed from the list due to undergoing transplant, but also growing numbers of adult candidates added to the list over the past 3 years. In 2014, 2679 heart transplants were performed, an increase of 28.4% since 2003, and the number of people living with a transplanted heart continued to increase. The number of new pediatric candidates added to the heart transplant waiting list increased to 593 in 2014. The number of pediatric heart transplants performed each year increased from 293 in 2003 to 410 in 2014. Almost 60% of pediatric candidates waiting on December 31, 2014, had been waiting for less than 1 year, compared with 43.0% in 2004. Among pediatric patients who underwent transplant in 2008‐2012, overall cumulative incidence of death at 1, 3, and 5 years was 9.2%, 14.7%, and 18.3%, respectively.